Biologically Synthesized Nanoparticles Studies on Their Antibacterial, Antifungal & Anticancer Activities: Characterization and Biological Applications of Biologically Synthesized NiO Nanoparticles (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The examination of XRD patterns is the most important instrument in nano research. The NiO nanoparticles were image using a high magnification SEM. FT-IR spectroscopy was used to demonstrate the establishment of the NiO bond throughout the synthesis. The existence of Ni-O bond was verified by the development of a prominent band at 620 cm1 in the FT-IR spectra. Furthermore, the Ni–O stretching vibration's distinctive absorption band validates the Ni–O-Ni mode. The band gap of NiO is calculated to be 3.06 eV. When compared to published values for bulk NiO particles and NiO thin films, the calculated values are lower than the published values. The qualities were validated by the band gap values.